Analisis Tingkat Kepuasan Mahasiswa Fakultas Sains dan Teknik Terhadap Pembelajaran Secara Daring Selama Masa Pandemi Covid 19 - Maria Kleden; Astri Atti; Mari Lobo (Jurnal LENTERA: Jurnal Studi Pendidikan, 2022)
This research aims to determine the level of satisfaction of students from the Faculty of Science and Engineering, Nusa Cendana University, Kupang towards bold learning which is measured from nine aspects, namely easy access, timeliness, giving learning objectives, materials, understanding theory, and skills, ease of sending assignments, opportunities. sending assignments, opportunities to ask questions and practice, lecturers are always in lectures and interact with fellow students. This type of research is a survey with a cross-sectional approach, where the data collection process is carried out at the same time for all variables. The instrument of this research is a questionnaire containing 23 questions which are the elaboration of 9 indicators of learning satisfaction. The conclusion of this study is that students of the Faculty of Science and Engineering expressed satisfaction with learning boldly. Of the 9 aspects studied, students expressed satisfaction with the aspect of punctuality, providing learning materials, opportunities to ask questions and being creative, and always in lectures. As for the other 4 aspects, students stated that they were quite satisfied.